2011
DOI: 10.1152/jn.00831.2010
|View full text |Cite
|
Sign up to set email alerts
|

CB1 modulation of temporally distinct synaptic facilitation among local circuit interneurons mediated by N-type calcium channels in CA1

Abstract: Ali AB. CB1 modulation of temporally distinct synaptic facilitation among local circuit interneurons mediated by N-type calcium channels in CA1. J Neurophysiol 105: 1051-1062, 2011. First published December 1, 2010; doi:10.1152/jn.00831.2010.-One of the critical factors in determining network behavior of neurons is the influence of local circuit connections among interneurons. The short-term synaptic plasticity and the subtype of presynaptic calcium channels used at local circuit connections of inhibitory inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…One can explain the presynaptic dependency of I→E and I→I dynamics by similar mechanisms. Indeed, differences in the subtypes of Ca 2+ channels in presynaptic terminals have been implicated in a study of facilitating and depressing synapses made, respectively, by cholecystokinin (CCK)-positive and CCK-negative interneurons in the hippocampus (Ali, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…One can explain the presynaptic dependency of I→E and I→I dynamics by similar mechanisms. Indeed, differences in the subtypes of Ca 2+ channels in presynaptic terminals have been implicated in a study of facilitating and depressing synapses made, respectively, by cholecystokinin (CCK)-positive and CCK-negative interneurons in the hippocampus (Ali, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Carbachol may enhance DSI by stimulating the firing of cholecystokinin‐positive GABA neurons (Kawaguchi, 1997; Cea‐del Rio et al 2010) that are the main source of cannabinoid‐sensitive synapses (Glickfeld & Scanziani, 2006; Neu et al 2007; Galarreta et al 2008; Lee et al 2010; Ali, 2011). However, synapses from some cholecystokinin‐positive cells onto pyramidal neurons are cannabinoid‐insensitive (Lee et al 2010; Ali, 2011) possibly because they lack CB1Rs (Eggan et al 2010). Moreover, carbachol also stimulates somatostatin‐ and vasoactive intestinal peptide‐positive GABA neurons (Kawaguchi, 1997; Fanselow et al 2008), which are not thought to provide cannabinoid‐sensitive synapses, although somatostatin neurons contain CB1R mRNA (Hill et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Carbachol may enhance DSI by stimulating the firing of cholecystokinin-positive GABA neurons (Kawaguchi, 1997;Cea-del Rio et al 2010) that are the main source of cannabinoid-sensitive synapses (Glickfeld & Scanziani, 2006;Neu et al 2007;Galarreta et al 2008;Lee et al 2010;Ali, 2011). However, synapses from some cholecystokinin-positive cells onto pyramidal neurons are cannabinoid-insensitive Ali, 2011) possibly because they lack CB1Rs .…”
Section: Figure 10 Daglα Deficiency Abolishes Dsi Induced By Action mentioning
confidence: 99%
“…Cell pairs used in the simulations were pulled out from a data-driven reconstruction of the rat 215 CA1 region, built with the pipeline presented in Markram et al (2015). Number of synapses per 216 connection for experimentally characterized pathways (Ali, 2011;Biro et al, 2005;Buhl et al, 217 1994a,b;Deuchars and Thomson, 1996;Földy et al, 2010;Maccaferri et al, 2000;Sik et al, 218 1995;Vida et al, 1998) (r = 0.98, Figure 2 b and Supplementary Table S3) along with targeting 219 profile (Figure 2 a) was verified for this work. PSP attenuation in the active dendrites of PCs 220 (Migliore et al, 2018) is also in line with the experimentally reported curves (Magee and Cook,221 2000) (Supplementary Figure S1).…”
mentioning
confidence: 61%